Differentiation of human umbilical cord-derived mesenchymal stem cells into epidermal-like cells - Chung, Doan Chinh; Long, Le Thanh; Son, Hoang Nghia; Chuong, Nguyen Hoang; Si, Do Minh; Dong, Le Van (Academia Journal of Biology, 2014)
Umbilical cord derived - mesenchymal stem cells (UCMSCs) can be readily obtained, avoid ethical debates or moral constraints, and show excellent pluripotency and proliferation potential. Therefore, the aim of this study was to examine the differentiation potential of UCMSCs into epidermal cells. In this study, UCMSCs were isolated by a tissue attachment culture method and characterized their immunophenotype and their differentiation potency. On the third passage, UCMSCs were induced to differentiate into epidermal cells in induction media. The results showed that UCMSCs exhibited a fibroblast-like morphology, owned strong proliferation and differentiation capacity into adipocytes and osteoblasts. Isolated UCMSCs were strong positive for CD73, CD90, CD105 and CD166, but not CD19, CD34, CD45 and HLA-DR. After differentiation, the induced cells had morphological changes when compared with the non-induced cells, and expressed CK18, CK19, and P63 whereas non-induced cells were not. Interestingly, both induced cells and non-induced cells expressed β1-intergrin. These results demonstrated that UCMSCs might trans-differentiate into epithelial cells in vitro under appropriate culture conditions. These cells may be useful for artificial skin tissue engineering in the future.